Local Political Strength in Khofifah Indar Parawansa's Win in the 2018 Governor Election for the Electoral District of East Java - Arianti Kusnadi; Ahmad Muhajir; Erlin Rizki; Fajar Baihaqi; Lusy Fany (Social Impact Journal, 2023)
The purpose of this writing is to analyze the political power of the caliph as a whole. Muslimat Nahdlatul Ulama is an organization that has always been active in supporting the khiffah in making political contention successful, this is also evidenced by the election of the Governor of East Java in 2018, nahdiyin residents participated in the victory starting from mass mobilization at the grassroots level to consolidation at the nahdiyin elite level. The research method used is a qualitative method that seeks to understand social phenomena in depth. The results of this discussion are concrete evidence that the NU organization is the largest community organization in Indonesia and that strong solidarity has become a source of political strength for the caliph. Apart from that, identity branding as a woman has succeeded in becoming a source of Khofifah's political strength. Khofifah is a successful female figure, even though Khofifah's brand identity is not instantaneous. There are many things that must be taken by Khofifah, including massive communication, also known as a clean political actor. Corruption, with a clean track record, is certainly a strength for Khofifah in increasing her electability, this will add to the weight of the voter's decision, especially in the rational voter segment.